The Role of Emotional Intelligence in Controlling Work Stress to Improve Work Performance in Generation Z - Desy Prastyani; Mariyana Widiastuti; Yuanita Arianti (Universitas Diponegoro, 2026)
The increasing number of Generation Z in the world of work shows different characteristics compared to previous generations, such as the level of sensitivity to work pressure, the need for a supportive work environment, and emotional adaptability which are important factors in supporting performance. This study aims to analyze the influence of emotional intelligence on work performance and the role of work stress as a mediating variable in Generation Z employees in the Greater Jakarta area. This study uses a quantitative approach with a survey method through the distribution of questionnaires to Generation Z employees who work in various industrial sectors. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results of the study show that emotional intelligence has a positive effect on work performance and a negative effect on work stress. However, work stress has no effect on work performance and is unable to mediate the relationship between emotional intelligence and work performance. These findings suggest that the improvement in performance of Generation Z employees is more influenced by an individual's ability to manage emotions than through work stress mechanisms.